2019
DOI: 10.1021/acsnano.8b08177
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Targeted Nanoparticle-Based Gene Delivery for Brain Tumor Therapy

Abstract: Targeted therapy against the programmed cell death ligand-1 (PD-L1) blockade holds considerable promise for the treatment of different tumor types; however, little effect has been observed against gliomas thus far. Effective glioma therapy requires a delivery vehicle that can reach tumor cells in the central nervous system, with limited systemic side effect. In this study, we developed a cyclic peptide iRGD (CCRGDKGPDC)-conjugated solid lipid nanoparticle (SLN) to deliver small interfering RNAs (siRNAs) agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(128 citation statements)
references
References 100 publications
(195 reference statements)
2
123
0
3
Order By: Relevance
“…This superior cell killing potential was also confirmed in animal studies. Several other pre‐clinical reports supported this favorable increased uptake for other particles such as nanocarriers composed of poly( N ‐(2‐hydroxypropyl)methacrylamide (HPMA) polymers, solid lipid nanocarriers and liposomes . These radiation effects were also proven to occur in humans as different clinical trials indicated higher tumor uptake of liposomes when combined with fractionated radiotherapy .…”
Section: Enhanced Targeting or Tumor Uptake In Concurrent Radiotherapmentioning
confidence: 83%
“…This superior cell killing potential was also confirmed in animal studies. Several other pre‐clinical reports supported this favorable increased uptake for other particles such as nanocarriers composed of poly( N ‐(2‐hydroxypropyl)methacrylamide (HPMA) polymers, solid lipid nanocarriers and liposomes . These radiation effects were also proven to occur in humans as different clinical trials indicated higher tumor uptake of liposomes when combined with fractionated radiotherapy .…”
Section: Enhanced Targeting or Tumor Uptake In Concurrent Radiotherapmentioning
confidence: 83%
“…Together with surgery and chemotherapy, radiotherapy is the third leg of GBM treatments. It has been shown that anti-GBM nano-formulations could enhance the effect of radiotherapy by: (i) increasing the downregulation of PD-L1 and EGFR using solid/lipid nanoparticles, resulting in a decrease of glioblastoma growth and prolonged mouse survival [41], (ii) enhancing the EPR effect, Nano-formulated anti-GBM drugs can also improve the efficacy of chemotherapy by increasing the activity of various anti-tumor drugs, such as: (i) secondary metabolites of algae, which induced cytotoxicity towards A-172 glioblastoma cells when loaded in nano-microparticles [83], (ii) arsenic trioxide, which enabled treating temozolomide (TMZ)-resistant GBM cells following their encapsulation in liposomes in the presence of Mn [84], (iii) carboplatin, which led to higher tumor cytotoxicity, reduced neuronal toxicity and prolonged tissue half-life on rat and porcine GBM model when they were associated with PLGA copolymer [68], (iv) chlorotoxin, whose efficacy was increased compared with free drugs when they were conjugated with iron oxide nanoparticle, a behavior attributed to nanoparticles leading to a longer blood half-life, a better ability to cross the BBB and a faculty to be internalized in cells without losing its therapeutic activity [85], (v) cisplatin, which could move within the porous extracellular matrix between GBM cells when loaded with PEG-coated nanoparticles, yielding deeper brain penetration than non-pegylated cisplatin, and resulting in an increased survival of rats bearing GBM by more than two weeks compared with Cisplatin alone [66], (vi) curcumin, whose bioavailability and water solubility were increased when they were encapsulated in a dendrosome, suppressing U87MG cells growth without affecting healthy cells [86], (vii) doxorubicin, which led to remission among 20% of rats bearing GBM treated with DOX bound to polysorbate-coated nanoparticles [87], (viii) paclitaxel, which was more efficiently transported through the BBB and led to an improved anti-proliferative efficacy when it was associated with NPs and specific peptides Pep-1 designed to cross the BBB than when it was free [88], (ix) temozolomide (TMZ), which did not denature and could be specifically delivered to GBM cells with the help of the targeting peptide chlorotoxin (CTX), leading to enhanced cytotoxicity towards GBM cells compared with free TMZ [89].…”
Section: Mechanisms Of Action Of Anti-gbm Nano-drugsmentioning
confidence: 99%
“…Together with surgery and chemotherapy, radiotherapy is the third leg of GBM treatments. It has been shown that anti-GBM nano-formulations could enhance the effect of radiotherapy by: (i) increasing the downregulation of PD-L1 and EGFR using solid/lipid nanoparticles, resulting in a decrease of glioblastoma growth and prolonged mouse survival [41], (ii) enhancing the EPR effect, leading to better diffusion of nanoparticles to GBM tumors [90], (iii) sensitizing GBM cells to radiation by making GBM stem cells enter the radiation sensitive G2/M phase using the Sonic hedgehog ligand [91], by increasing DNA double-strand breaks using BSA-Au nanoparticles [92], or by exposing iodine nanoparticles to radiations [93], and (iv) enhancing the expression of the targets of CTX (i.e., MMP-2 and ClC-3), as well as BBB permeability and cellular internalization, leading to GBM tumor growth inhibition in vivo, using PLGA nanoparticles conjugated to chlorotoxin (CTX) [94]. The radio-sensitizing effect, which is often sought for when exposing nanoparticles to X-rays, is usually described as being optimal for nanoparticles of high atomic number Z, due to certain physical effects such as photoelectric ones, which are enhanced at high Z values.…”
Section: Mechanisms Of Action Of Anti-gbm Nano-drugsmentioning
confidence: 99%
“…Due to the presence of a blood-brain barrier, immune cells are not thought to be resident in the central nervous system [49]. However, after clearing a viral infection in the central nervous system, some of the antigen-specific CD8+ T cells maintained in the brain as TRM cells [50].…”
Section: Locationmentioning
confidence: 99%